Ascertaining the Francophone population in Ontario: validating the language variable in health data - Batista, Ricardo; Hsu, Amy T.; Bouchard, Louise; Reaume, Michael; Rhodes, Emily; Sucha, Ewa; Guerin, Eva; Prud'homme, Denis; Manuel, Douglas G.; Tanuseputro, Peter (BMC Medical Research Methodology, 2024)
Abstract Background Language barriers can impact health care and outcomes. Valid and reliable language data is central to studying health inequalities in linguistic minorities. In Canada, language variables are available in administrative health databases; however, the validity of these variables has not been studied. This study assessed concordance between language variables from administrative health databases and language variables from the Canadian Community Health Survey (CCHS) to identify Francophones in Ontario.

Quality and safety in long-term care in Ontario: The impact of language discordance - Batista, Ricardo; Prud'homme, Denis; Rhodes, Emily; Hsu, Amy; Talarico, Robert; Reaume, Michael; Guérin, Eva; Bouchard, Louise; Desaulniers, Jacinthe; Manuel, Douglas; Tanuseputro, Peter (Journal of the American Medical Directors Association, 2021)
Objectives This study compared quality indicators across linguistic groups and sought to determine whether disparities are influenced by resident-facility language discordance in long-term care. Design Population-based retrospective cohort study using linked databases. Setting and Participants Retrospective cohort of newly admitted residents of long-term care facilities in Ontario, Canada, between 2010 and 2016 (N=47,727). Individual residents' information was obtained from the Resident Assessment Instrument Minimum Data Set (RAI-MDS) to determine resident's primary language, clinical characteristics, and health care indicators. Measures Main covariates of interest were primary language of the resident and predominant language of the long-term care facility, which was determined using the French designation status as defined in the French Language Services Act. Primary outcomes were a set of quality and safety indicators related to long-term care: worsening of depression, falls, moderate-severe pain, use of antipsychotic medication, and physical restraints. Multivariable logistic regression models were used to assess the impact of resident's primary language, facility language, and resident-facility language discordance on each quality indicator. Results Overall, there were few differences between francophones and anglophones for quality and safety indicators. Francophones were more likely to report pain (10.9% vs 9.9%; P = .001) and be physically restrained (7.3% vs 5.2%; P < .001), whereas a greater proportion of anglophones experienced worsening of depressive symptoms (24.0% vs 22.9%; P = .001). However, quality indicators were generally worse for francophones in Non-Designated facilities, except for pain, which was more commonly reported by francophones in French-Designated facilities. Anglophones were more likely to be physically restrained in French-Designated facilities (6.7% vs 5.1%; P < .001). Conclusions and Implications For francophones, quality indicators tended to be worse in the presence of resident-facility language discordance. However, these findings did not persist after adjusting for individual- and facility-level characteristics, suggesting that the disparities observed at the population level cannot be attributed to linguistic factors alone.

Prevalence and patterns of multimorbidity among linguistic groups of patients receiving home care in Ontario: a retrospective cohort study. - Batista, Ricardo; Reaume, Michael; Roberts, Rihannon; Seale, Emily; Rhodes, Emily; Sucha, Ewa; Pugliese, Michael; Kendall, Claire E.; Bjerre, Lise M.; Bouchard, Louise; Prud'homme, Denis; Manuel, Douglas G.; et al. (BMC Geriatr., 2023)
Background Prior studies have demonstrated the negative impact of language barriers on access, quality, and safety of healthcare, which can lead to health disparities in linguistic minorities. As the population ages, those with multiple chronic diseases will require increasing levels of home care and long-term services. This study described the levels of multimorbidity among recipients of home care in Ontario, Canada by linguistic group. Methods Population-based retrospective cohort of 510,685 adults receiving home care between April 1, 2010, to March 31, 2018, in Ontario, Canada. We estimated and compared prevalence and characteristics of multimorbidity (2 or more chronic diseases) across linguistic groups (Francophones, Anglophones, Allophones). The most common combinations and clustering of chronic diseases were examined. Logistic regression models were used to explore the main predictors of ‘severe’ multimorbidity (defined as the presence of five or more chronic diseases). Results The proportion of home care recipients with multimorbidity and severe multimorbidity was 92% and 44%, respectively. The prevalence of multimorbidity was slightly higher among Allophones (93.6%) than among Anglophones (91.8%) and Francophones (92.4%). However, Francophones had higher rates of cardiovascular and respiratory disease (64.9%) when compared to Anglophones (60.2%) and Allophones (61.5%), while Anglophones had higher rates of cancer (34.2%) when compared to Francophones (25.2%) and Allophones (24.3%). Relative to Anglophones, Allophones were more likely to have severe multimorbidity (adjusted OR = 1.04, [95% CI: 1.02–1.06]). Conclusions The prevalence of multimorbidity among Ontarians receiving home care services is high; especially for whose primary language is a language other than English or French (i.e., Allophones). Understanding differences in the prevalence and characteristics of multimorbidity across linguistic groups will help tailor healthcare services to the unique needs of patients living in minority linguistic situations.

Impact of patient–family physician language concordance on healthcare utilisation and mortality: A retrospective cohort study of home care recipients in Ontario, Canada. - Reaume, Michael; Batista, Ricardo; Sucha, Ewa; Pugliese, Michael; Roberts, Rhiannon; Rhodes, Emily; Seale, Emily; Kendall, Claire. E.; Bjerre, Lise; Bouchard, Louise; Johnson, Sharon; Sood, Manish; et al. (BMJ Public Health, 2024)
Introduction As the world’s linguistic diversity continues to increase at an unprecedented rate, a growing proportion of patients will be at risk of experiencing language barriers in primary care settings. We sought to examine whether patient–family physician language concordance in a primary care setting is associated with lower rates of hospital-based healthcare utilisation and mortality. Methods We conducted a population-based retrospective cohort study of 497 227 home care recipients living in Ontario, Canada. Patient language was obtained from home care assessments while physician language was obtained from the College of Physicians and Surgeons of Ontario. We defined primary care as language concordant when patients and their rostered family physicians shared a mutually intelligible language, and we defined all other primary care as language discordant. The primary outcomes were Emergency Department (ED) visits, hospitalisations and death within 1 year of index home care assessment. Results Compared with non-English, non-French speakers who received language-discordant primary care, those who received language-concordant primary care experienced fewer ED visits (53.1% vs 57.5%; p<0.01), fewer hospitalisations (35.0% vs 37.6%; p<0.01) and less mortality (14.4% vs 16.6%; p<0.01) during the study period. In multivariable regression analyses, non-English, non-French speakers had lower risks of ED visits (adjusted hazard ratio [aHR] 0.91, 95% CI 0.88 to 0.94), hospitalisations (aHR 0.94, 95% CI 0.90 to 0.98) and death (aHR 0.87, 95% CI 0.82 to 0.93) when they received language-concordant primary care. For francophones, the risk of experiencing an ED visit, a hospitalisation or death was not impacted by the language of their family physician. Conclusions Patient–family physician language concordance is associated with a lower risk of adverse outcomes in non-English and non-French speakers. Optimising the delivery of language-concordant care could potentially result in significant decreases in the use of acute healthcare services and mortality at the population level.